Renewable energy sources in transnational cooperation in the Baltic Sea Region - Studzieniecki , Tomasz; Palmowski, Tadeusz (Bulletin of Geography. Socio-economic Series, 2022)
The implementation of the EU Strategy for the Baltic Sea Region has made the use of renewable energy sources a priority. The Region has always been economically and ecologically very diverse. The development of transnational cooperation became an opportunity to bridge the existing disparities and support renewable energy development. The aim of the article is to answer the question how the transnational cooperation implemented under the EU Cohesion Policy could contribute to BSR energy transition. The authors elaborated a research model, which presents a sequence of activities. The research used secondary sources, including KEEP data. EU. EUROSTAT, EUSBSR. The article examined the cooperation carried out within 41 projects financed under seven territorial cooperation programs in the BSR in the period 2000-2020. The research results are presented in terms of the subject, subject and space with the visualization made on the basis of NUTS 2 and NUTS 3 units